Client-centred practice: Perspectives of persons with a traumatic brain injury. (2nd January 2016) - D'Cruz, Kate; Howie, Linsey; Lentin, Primrose
Abstract: Background : Client-centred practice is well established as a core foundation of occupational therapy; however, there is little research evidence concerning the client experience. Objectives : To understand client-centred practice from the perspective of adults with a traumatic brain injury (TBI) participating in community-based occupational therapy. Methods : Six adults with a moderate–severe TBI participated in two semi-structured, qualitative interviews each. In total 12 interview transcripts and additional data were coded using constructivist grounded theory methods. Results : Data analysis produced three main themes and sub-themes: (i) Experiencing the client–therapist relationship: Seeing me as the person I was; Getting to know me in the now; Making a positive connection; (ii) Actively participating in therapy: Valuing the therapist; Being partners in therapy; and (iii) Finding my place in life: Adjusting to who I am now and Sharing my journey. Conclusion : The results present a framework for understanding client-centred practice as a person-centred process of engagement between the client and the therapist, as informed from the client perspective. Significance : Occupational therapists are encouraged to value and invest in the development of relationships with clients whilst the importance of seeking and integrating the client perspective into practice and research is affirmed for the profession.